PERLINDUNGAN HUKUM OLEH PEMERINTAH DI MASA PANDEMI COVID-19 - Wahyuni (Universitas Tadulako, 2024)
The importance of legal protection by the government during the Covid-19 pandemic is currently increasingly being felt by the public as elements affected both directly and indirectly. Based on data released by the Ministry of Health of the Republic of Indonesia regarding the soaring spread of Covid-19, the government is increasingly being placed in the position most responsible for legal protection of the rights of its people. With unusual conditions like this, of course the government needs to make extraordinary efforts to address the emergency of Covid-19 transmission by establishing legal regulations and decisions. The government's authority to issue policies is felt to be even more massive when the facts on the ground show conditions of rejection and indifference by the public. This condition ultimately inspired the author to carry out a normative-empirical legal analysis using legal materials and field data and then draw descriptive conclusions. Various efforts and legal steps have been taken by the government, both the central government and regional governments, to overcome the emergency of the Covid-19 outbreak, however, however legal protection efforts are provided without the role and awareness of the community, these efforts will not provide effective results. What we can avoid is when the government then takes firm steps by implementing sanctions for those who are not cooperative, with efforts to increase the legal awareness of the entire community regarding the dangers of this virus so that they actually take action that is in line with efforts to overcome Covid-19.